Kristalisasi Nilai Pendidikan Islam dalam Tradisi Melaut di Kecamatan Teunom, Aceh Jaya - Habibi MZ, Muhammad; Fauzani, Laitani; Kurniawan, Zeka (FITRAH: International Islamic Education Journal, 2024)
Islamic education plays a crucial role in shaping the character of individuals and communities through the internalization of religious values. Local traditions serve as an effective medium for instilling these values practically in everyday life. This study analyzes the crystallization of Islamic educational values within the maritime tradition (adat laot) in Teunom District, Aceh Jaya, focusing on three main aspects: (1) The existence of the maritime tradition in the community; (2) The substance of educational values within the maritime tradition; and (3) The essence of Islamic educational values in the maritime tradition. This research employs a qualitative approach, with descriptions presented in a descriptive-analytical manner. Data were collected through in-depth interviews with traditional leaders, religious figures, fishermen, and local community members, as well as through participatory observation and documentary studies. Data analysis was conducted thematically using the Miles & Huberman approach to identify patterns of Islamic value internalization. The findings reveal that the existence of the maritime tradition is reflected in three main aspects: (1) The aspect of prohibited fishing days, which carries the nuance of beu ta jaga (must be observed), reflecting adherence to traditional and religious rules; (2) The aspect of social activities among fishermen, which embodies beu ta ingat (must be remembered), fostering solidarity and social care; and (3) The aspect of customary social sanctions, which embodies beu ta thee droe (must be self-aware), reinforcing justice and collective agreement. From these three aspects, five essences of Islamic educational values were identified: (1) The value of obedience in worship; (2) The value of ta’awun (mutual assistance) and ukhuwah islamiyyah (Islamic brotherhood); (3) The value of al-‘adl (justice) and shura (consultation); (4) The value of hifz al-bi’ah (environmental preservation); and (5) The value of gratitude. The crystallization of Islamic educational values occurs through three stages: (1) Internalization of values through social interaction and exemplary behavior; (2) Transformation of values in daily life; and (3) Institutionalization of values into deeply rooted customary norms. Thus, the maritime tradition in Teunom serves as a vehicle for Islamic education based on local wisdom, remaining relevant in shaping the character of coastal communities. Abstrak Pendidikan Islam berperan penting dalam membentuk karakter individu dan masyarakat melalui internalisasi nilai-nilai keagamaan. Tradisi lokal berperan sebagai medium pendidikan yang efektif dalam menanamkan nilai-nilai secara praktis dalam kehidupan sehari-hari. Penelitian ini menganalisis kristalisasi nilai pendidikan Islam dalam tradisi melaut (adat laot) di Kecamatan Teunom, Aceh Jaya, dengan fokus pada tiga aspek utama: (1) Eksistensi tradisi melaut dalam masyarakat; (2) Substansi nilai pendidikan dalam tradisi melaut; dan (3) Esensi nilai pendidikan Islam dalam tradisi melaut. Penelitian ini menggunakan pendekatan kualitatif dimana uraian yang dilakukan secara deskriptif-analitis. Data dikumpulkan melalui wawancara mendalam dengan tokoh adat, tokoh agama, nelayan, dan masyarakat setempat, serta melalui observasi partisipatif dan studi dokumentasi. Analisis data dilakukan secara tematik guna mengidentifikasi pola kristalisasi nilai-nilai Islam. Hasil penelitian menunjukkan bahwa eksistensi tradisi melaut tercermin dalam tiga aspek utama: (1) aspek hari-hari pantangan melaut bernuansa beu ta ingat untuk merefleksikan kepatuhan terhadap aturan adat dan keagamaan; (2) aspek aktivitas sosial sesama nelayan berdimensi beu ta jaga yang menumbuhkan solidaritas dan kepedulian sosial; (3) aspek sanksi adat sosial yang berdimensi beu ta thee droe untuk memperkuat keadilan dan kesepakatan bersama. Dari ketiga aspek ini, teridentifikasi lima esensi nilai pendidikan Islam, (1) nilai ketaatan dalam ibadah; (2) nilai ta’awun dan ukhuwah islamiyyah; (3) nilai al-‘adl dan syura; (4) nilai hifz al-‘alam; (5) nilai syukur. Kristalisasi nilai pendidikan Islam dalam tradisi melaut terjadi melalui tiga tahapan: (1) Internalisasi nilai melalui interaksi sosial dan keteladanan; (2) Transformasi nilai dalam kehidupan sehari-hari; dan (3) Institusionalisasi nilai dalam norma adat yang mengakar dalam masyarakat. Kesimpulannya, tradisi melaut di Teunom berperan sebagai medium kristalisasi pendidikan Islam berbasis kearifan lokal yang relevan dalam membentuk karakter masyarakat.